Efficient bandwidth allocation methods in upstream EPON - Sadon S.K.; Din N.M.; Radzi N.A.; Yaacob M.B.; Maier M.; Al-Mansoori M.H. (Springer Netherlands, 2023)
The Internet has become the world’s leading universal global communication infrastructure. Optical solutions are sought after at the access network to support the ever increasing demand in bandwidth. Passive Optical Networks (PONs) are seen to provide a cost effective solution for this. PON Dynamic Bandwidth Allocation (DBA) scheme provides the means for upstream traffic allocation. In this paper, the operation of several bandwidth allocation algorithms in upstream Ethernet PON (EPON) is presented. An Efficient Distributed DBA (EDDBA) that supports Quality of Service (QoS) for both inter and intra ONU allocation is proposed. The proposed scheme introduces an identical DBA algorithm running simultaneously in each ONU. The simulation performance for the proposed DBA was conducted using Prolog and shows flexibility, reliability in handling data, voice, and video traffic. © Springer Science+Business Media Dordrecht 2014.